Music and Marketing - North, Adrian; Hargreaves, David (Oxford University Press, 2009)
This chapter summarizes the many ways in which music and marketing relate to one another. It argues that the range of the effects that music can have on consumer behaviour is striking. The available research suggests that the ‘right’ kinds of music can typically lead to increases in turnover of around 10 per cent, such that piped music makes clear commercial sense. Note also that different types of music very clearly have different effects. Businesses cannot regard music as a homogeneous sonic mass.